PENGARUH DISIPLIN KERJA, MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. BPR SWADAYA ANAK NAGARI PASAMAN BARAT - Putri Ika Yunia; Taufiqurahman2 Taufiqurahman2; Roesdi Roesnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to examine the effect of work discipline, motivation and compensation on employee performance. Collecting data in this study using a questionnaire survey with sampling techniques for this study using a census (saturated) by taking all members of the population, then made a sample. The questionnaire was distributed to 58 respondents in the marketing department of PT. BPR Swadaya Anak Nagari Pasaman Barat, so that it can be used and processed as a whole. The data collected is processed using Multiple Linear Regression between Work Discipline, Motivation and Compensation for Employee Performance. The results showed that: 1) discipline has a positive and significant effect on employee performance at PT. BPR Swadaya Anak Nagari Pasaman Barat. 2) motivation has a positive and significant effect on the performance of PT. BPR Swadaya Anak Nagari Pasaman Barat 3) compensation has a positive and significant effect on employee performance at PT. BPR Swadaya Anak Nagari Pasaman Barat 4) Work Discipline, Motivation and Compensation have a positive and significant effect on the Performance of PT. BPR Swadaya Anak Nagari Pasaman Barat.Keywords : Works Discipline, Motivation, Compensation, Employee Performance